2017
DOI: 10.3892/ol.2017.6334
|View full text |Cite
|
Sign up to set email alerts
|

Poly (ADP-ribose) polymerase-1 inhibition decreases proliferation through G2/M arrest in esophageal squamous cell carcinoma

Abstract: Poly (ADP-ribose) polymerase-1 (PARP1) plays a vital role in DNA repair and is expected to be an effective target in various malignancies. The aim of the present study was to investigate the clinical and biological significance of PARP1 expression in esophageal squamous cell carcinoma (ESCC). Immunohistochemical (IHC) staining was used to examine the association between PARP1 expression and the clinicopathological features of 86 patients with ESCC. The antitumor effect of small interfering RNA against PARP1 (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…It is well known that the core of the cell cycle regulation mechanism is a group of cell cycle dependent protein kinase (CDKs), which is dependent on their regulatory subunit cyclins. Cyclin E and CDK2 are major regulators of cell cycle checkpoint and their interaction triggers the entry into the S phase, while cyclin B1‐CDK1 is potential to promote cell cycle progression from the S phase to G 2 /M phase . ADP has been reported to inhibit proliferation of the human lung adenocarcinoma cells via the induction of massive accumulation of cells in the S phase .…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the core of the cell cycle regulation mechanism is a group of cell cycle dependent protein kinase (CDKs), which is dependent on their regulatory subunit cyclins. Cyclin E and CDK2 are major regulators of cell cycle checkpoint and their interaction triggers the entry into the S phase, while cyclin B1‐CDK1 is potential to promote cell cycle progression from the S phase to G 2 /M phase . ADP has been reported to inhibit proliferation of the human lung adenocarcinoma cells via the induction of massive accumulation of cells in the S phase .…”
Section: Discussionmentioning
confidence: 99%
“…25 In addition, a Phase II study of the EGFR tyrosine kinase inhibitor icotinib reported a 16.6% overall response rate (ORR) and a 46.3% disease control rate in oesophageal squamous cell carcinomas with either high EGFR expression on IHC or amplification on FISH. 26 Based on laboratory studies of oesophageal squamous cell carcinoma, several other potential novel therapeutic targets exist, 20 including CDK4/6, 27 poly (ADP-ribose) polymerase-1 (PARP), 28,29 the NRF2 signalling pathway 30 and the Wnt signalling pathway. 31 However, given current treatment guidelines, pathologists have little role to play regarding targeted therapy for oesophageal squamous cell carcinoma other than outside PD-L1 immunohistochemical staining, if requested.…”
Section: Oesophageal Squamous Cell Carcinomamentioning
confidence: 99%
“…Based on laboratory studies of oesophageal squamous cell carcinoma, several other potential novel therapeutic targets exist, 20 including CDK4/6, 27 poly(ADP‐ribose) polymerase‐1 (PARP), 28,29 the NRF2 signalling pathway 30 and the Wnt signalling pathway 31 . However, given current treatment guidelines, pathologists have little role to play regarding targeted therapy for oesophageal squamous cell carcinoma other than outside PD‐L1 immunohistochemical staining, if requested.…”
Section: Oesophageal Squamous Cell Carcinomamentioning
confidence: 99%
“…In general, ADP-ribosyltransferases are responsible for regulation of intracellular and extracellular signal transduction. Therefore, their activity determines viability and proliferation potential of cells, DNA stability, immune system reactivity and thus the proper functioning of eukaryotic organisms ( Bai, 2015 ; Corda & Di Girolamo, 2002 ; De Vos, Schreiber & Dantzer, 2012 ; Yamamoto et al, 2017 ). On the other hand, ADP-ribosyltransferases may also be involved in development of pathological states such as neurodegenerative disorders, diabetes, atherosclerosis, cataract and cancer ( Barreiro & Gea, 2018 ; Gunderson & Moore, 2015 ; Kamboj et al, 2013 ; Malyuchenko et al, 2015 ; Mangerich & Bürkle, 2012 ; Rossi, Ghosh & Bohr, 2010 ).…”
Section: Introductionmentioning
confidence: 99%